2020
DOI: 10.3390/ijms21197236
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Simvastatin on Endotoxin-Induced Acute Kidney Injury through Activation of Tubular Epithelial Cells’ Survival and Hindering Cytochrome C-Mediated Apoptosis

Abstract: Increasing evidence suggests that apoptosis of tubular cells and renal inflammation mainly determine the outcome of sepsis-associated acute kidney injury (AKI). The study aim was to investigate the molecular mechanism involved in the renoprotective effects of simvastatin in endotoxin (lipopolysaccharide, LSP)-induced AKI. A sepsis model was established by intraperitoneal injection of a single non-lethal LPS dose after short-term simvastatin pretreatment. The severity of the inflammatory injury was expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
(76 reference statements)
2
26
0
Order By: Relevance
“…Excessive ROS can stimulate p53 that induces apoptosis. Moreover, B-cell lymphoma-2-associated X (Bax) is activated by ROS and/or p53 and translocated to the outer membrane of the mitochondria, leading to the leakage of cytochrome c (cyto c), which is a strong inducer of apoptosis ( 49 ). Therefore, the apoptosis signaling pathway is closely related to sepsis-AKI, and inhibiting apoptosis may be an effective strategy for the prevention and treatment of sepsis-AKI.…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…Excessive ROS can stimulate p53 that induces apoptosis. Moreover, B-cell lymphoma-2-associated X (Bax) is activated by ROS and/or p53 and translocated to the outer membrane of the mitochondria, leading to the leakage of cytochrome c (cyto c), which is a strong inducer of apoptosis ( 49 ). Therefore, the apoptosis signaling pathway is closely related to sepsis-AKI, and inhibiting apoptosis may be an effective strategy for the prevention and treatment of sepsis-AKI.…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…The contribution of TNF-α to renal damage was confirmed using TNFR1 −/− in endotoxemia, which prevents inflammation and apoptosis [51]. In addition, the in-creased expression of casp-3 cleavage has been detected in endotoxin-and CLP-induced AKI [52,53], along with higher renal IL-1β levels in cisplatin-associated AKI [54]. It is known that IL-1β activates nuclear factor kappa B pathway, playing an important role in the transcription of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 91%
“…In this current Special Edition, thirteen original research articles are presented: twelve in vivo studies in a murine or rat model and one in vitro study [ 3 ]. Seven studies show results from AKI models [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], five from fibrosis models (or CKD models) [ 9 , 11 , 12 , 13 , 14 ] and two from a transplant rejection model [ 4 , 15 ] (two studies used two different in vivo models).…”
mentioning
confidence: 99%
“…The study revealed a novel mechanism limiting the migration of lymphocytes to the site of inflammation during glomerulonephritis [ 7 ]. The findings of Nežić and coworkers investigated the molecular mechanism involved in the reno-protective effects of simvastatin in an endotoxin-induced AKI model [ 5 ]. The study indicated that simvastatin, a well-known lipid-lowering medication, has cytoprotective effects on induced tubular apoptosis, mediated by the upregulation of cell survival molecules and inhibition of the mitochondrial proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation